Analisis Pengaruh Social Media Marketing Terhadap Purchase Intention Dengan Perceived Value Sebagai Variabel Mediasi - Linardi, Filbert (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
As one of the largest retail anime hobby shops in Indonesia, Kyou Hobby Shop is required to be able to sell its products as many as possible to its customers. with optimum social media marketing, the shop can expect to benefit most from increases in its customers’ purchase intention and perceived value. The objective of this research is to identify the effects of social media marketing on purchase intention through perceived value as the mediating variable. The data of this quantitative research was harvested from questionnaires distributed to 120 respondents and was analyzed using SmartPLS. This study finds that social media marketing positively and significantly influences perceived value and purchase intention, that perceived value positively and significantly affects purchase intention, and that social media marketing positively and significantly impacts purchase intention through the mediation of perceived value. Abstrak Kyou Hobby Shop sebagai salah satu toko retail hobi Anime terbesar di Indonesia diharuskan mampu untuk menjual produk sebanyak-banyaknya kepada konsumen. Maka dari itu, Kyou Hobby Shop harus dapat meningkatkan purchase intention dan perceived value konsumen. Melalui social media marketing yang maksimal, Kyou Hobby Shop diharapkan dapat meningkatkan purchase intention dan perceived value konsumen setinggi mungkin. Penelitian ini bertujuan untuk mengetahui pengaruh social media marketing terhadap perceived value dan purchase intention. Metode yang digunakan dalam penelitian ini menggunakan metode kuantitatif, data dikumpulkan dengan melakukan penyebaran kuesioner kepada 120 responden. Data yang telah dikumpulkan akan diolah menggunakan software Smart-PLS. Hasil dari penelitian ini menunjukkan social media.